Analysis of magnetic structures in JANA2020 - Henriques, M S; Petříček, V; Goswami, S; Dušek, M (Acta crystallographica Section B, Structural science, crystal engineering and materials, 2024)
JANA2020 is a program developed for the solution and refinement of regular, twinned, modulated, and composite crystal structures. In addition, JANA2020 also includes a magnetic option for solving magnetic structures from powder and single-crystal neutron diffraction data. This tool uses magnetic space and superspace symmetry to describe commensurate and incommensurate magnetic structures. The basics of the underlying formulation of magnetic structure factors and the use of magnetic symmetry for handling modulated and non-modulated magnetic structures are presented here, together with the general features of the magnetic tool. Examples of structures solved in the magnetic option of JANA2020 are given to illustrate the operation and capabilities of the program.
Keywords: superspace; crystallography; magnetism; modulations